Contextual Pesantren Leadership Dynamics: A Comparative Study on the Adaptation of Innovative Psychological Profiles - Caria, Yameena Barica; Maaysa, Chellam (Development: Studies in Educational Management and Leadership, 2025)
This study provides an in-depth analysis of leadership profiles characterized by dynamic enthusiasm, a strong drive for change, and broad social orientation. However, this profile also shows impulsive tendencies, a lack of systematicity, a lack of attention to detail, and a high degree of autonomy from the applicable rules. The analysis is situated in the context of pesantren management in Indonesia. Using comparative case studies of the Darun Najah Pesantren in Jakarta and Ar Raudlatul Hasanah Pesantren in Medan, this study examines how these characteristics emerge and interact in a traditional institutional environment. The findings show that this leadership profile has the potential to encourage modernization and innovation in Islamic boarding schools through charisma, a strong task orientation, and the ability to build strong relationships. However, its overall effectiveness is highly dependent on the institution's capacity to overcome the inherent weaknesses of the leader. Mitigation is carried out through a competent support team with a focus on detailed planning, procedural management, and leadership development. Comparatively, Islamic boarding schools in urban environments such as Darun Najah are more adaptive in accommodating leaders' weaknesses, while more traditional environments such as Ar Raudlatul Hasanah require more careful mitigation strategies. Practically, this study provides guidance for Islamic boarding school administrators to optimize the potential of innovative leaders while managing the risks. Academically, this study contributes a model of psychological profile-based leadership analysis in the context of religious institutions, thereby enriching the study of educational management and organizational psychology.